Design, synthesis and evaluation of MCH receptor 1 antagonists—Part II: Optimization of pyridazines toward reduced phospholipidosis and hERG inhibition. Issue 16 (15th August 2015) - Roth, Gerald J.; Heckel, Armin; Kley, Jörg T.; Lehmann, Thorsten; Müller, Stephan G.; Oost, Thorsten; Rudolf, Klaus; Arndt, Kirsten; Budzinski, Ralph; Lenter, Martin; Lotz, Ralf R.H.; Schindler, Marcus; et al.
Graphical abstract